Pension Law - Hanin, Frédéric (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "Pension Law," by Ari N. Kaplan.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Pension plans; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z